2013
DOI: 10.1111/tpj.12363
|View full text |Cite
|
Sign up to set email alerts
|

AGAMOUSLIKE13, a putative ancestor for theEfunctional genes, specifies male and female gametophyte morphogenesis

Abstract: SUMMARYArabidopsis AGL13 is a member of the AGL6 clade of the MADS box gene family. GUS activity was specifically detected from the initiation to maturation of both pollen and ovules in AGL13:GUS Arabidopsis. The sterility of the flower with defective pollen and ovules was found in AGL13 RNAi knockdown and AGL13 + SRDX dominant-negative mutants. These results indicate that AGL13 acts as an activator in regulation of early initiation and further development of pollen and ovules. The production of similar floral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 60 publications
(67 reference statements)
1
38
1
Order By: Relevance
“…The AGL6 clade of MADS-box genes is very similar to the closely related E class MADS-box genes and could serve as a scaffold to interact with other A, B, C and D class MADS-box transcription factors to form combinatorial quaternary complexes [5759]. Dominant loss of function of the AGL6 clade of MADS-box genes by fusing a conserved suppressing motif to the proteins resulted in much smaller floral organs and partial sterility in Arabidopsis [58, 60]. SITDR8 is another clade of MADS-box genes, which was not found in Arabidopsis [61].…”
Section: Discussionmentioning
confidence: 99%
“…The AGL6 clade of MADS-box genes is very similar to the closely related E class MADS-box genes and could serve as a scaffold to interact with other A, B, C and D class MADS-box transcription factors to form combinatorial quaternary complexes [5759]. Dominant loss of function of the AGL6 clade of MADS-box genes by fusing a conserved suppressing motif to the proteins resulted in much smaller floral organs and partial sterility in Arabidopsis [58, 60]. SITDR8 is another clade of MADS-box genes, which was not found in Arabidopsis [61].…”
Section: Discussionmentioning
confidence: 99%
“…The related studies indicated that the AGAMOUS-LIKE 6 ( AGL6 ) gene played an essential role in the floral development (Rijpkema et al, 2009). In Arabidopsis thaliana, AGL6 gene was mainly expressed in the ovule and not expressed in the stamens (Schauer et al, 2009), however, the AGL13 gene was expressed in both ovule and stamens, and had the function of regulating stamen and pistil development (Hsu et al, 2014). In addition, the AGL23 gene had an effect on the female gametophyte development (Colombo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In these complexes, MADS box protein dimers may associate with other MADS dimers, but also with other transcriptional activators or repressors and chromatin remodelers (Hsu et al 2014;Pajoro et al 2014;Brambilla et al 2007;). …”
Section: Multimeric Interactions Of Floral Homeotic Mads Box Proteinsmentioning
confidence: 98%
“…Meanwhile, several other protein complexes including floral homeotic MADS box proteins have been identified, composed of only MADS box proteins or including proteins of other TF or transcription modulating families: AGL13, a protein related in sequence to the SEP proteins is able to replace SEP3 in an PI-AP3-AG-AGL13 complex and (AG-AGL13) 2 (Hsu et al 2014). However, the range of dimeric interactions of AGL13 is limited to four proteins only, including SHP1 and AG as floral homeotic proteins only indicating that AGL13 may not be able to fully complement for SEP protein function.…”
Section: Multimeric Interactions Of Floral Homeotic Mads Box Proteinsmentioning
confidence: 99%